(untitled) (Research, Society and Development, 2021)
The theoretical essay aims to present the role of Dependency Theory and its reflexes in the process of Brazilian socio-cultural construction. It also reflects on the role of educational economic organizations and their influence on Brazilian educational policy, as well as the actions of business reformers and the standardization of education. From a methodological point of view, this essay was constituted from a qualitative approach, produced through bibliographic research and documentary analysis. In order to give materiality to this theoretical essay, the following authors were privileged in the readings: Araújo and Frigotto (2015), Moura, Leite and Ribeiro (2015), Neves and Pronko (2008), Oriques (1995) among others. It is considered that, in the current moment of Brazilian educational policy, we have educational economic organizations that hide their real purposes of creation. They spread ideals to promote education for all, offered in a linear, stratified, statically created way, designed to serve specific audiences. The latent concern of major world banks to enter the educational market is viewed with great concern by parts of educational institutions and their teaching staff. The financing linked to the fulfillment of requirements, of goals to be achieved, reveal a trend of eminently ideological basis: servitude to the market.